1989
DOI: 10.1111/j.1469-8749.1989.tb04026.x
|View full text |Cite
|
Sign up to set email alerts
|

Development Offeedback and Feedforward Control of Upright Stance

Abstract: SUMMARY Feedback and feedforward (anticipatory) adjustments of stance were investigated in 58 children with normal development aged between seven months and 14 years, and in 14 children with motor and mental retardation aged between 21 months and seven years. Feedback responses after tilting the body were elicited in all but the two youngest children, aged seven and nine months. The observed rapid decrease in feedback response latency with age suggests considerable acceleration of central transmission. Effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…This indicates that children aged between 5 and 11 years can stabilize their posture during a load-lifting task by means of feed-forward control of APA before the onset of voluntary movement. This result is in line with previous studies on the development of anticipatory postural control using different types of self-initiated movements (arm pulling: Forssberg andNashner 1982, Hirschfeld andarm raising: Hay and Redon 2001;reaching: Van der Fits et al 1998; standing on tip-toes: Haas et al 1989; initiation of step: Ledebt et al 1998). APA are consistently used from the second postnatal year onwards and by 6 years of age they acquire functional significance.…”
Section: Development Of Parametric and Temporal Controlsupporting
confidence: 81%
“…This indicates that children aged between 5 and 11 years can stabilize their posture during a load-lifting task by means of feed-forward control of APA before the onset of voluntary movement. This result is in line with previous studies on the development of anticipatory postural control using different types of self-initiated movements (arm pulling: Forssberg andNashner 1982, Hirschfeld andarm raising: Hay and Redon 2001;reaching: Van der Fits et al 1998; standing on tip-toes: Haas et al 1989; initiation of step: Ledebt et al 1998). APA are consistently used from the second postnatal year onwards and by 6 years of age they acquire functional significance.…”
Section: Development Of Parametric and Temporal Controlsupporting
confidence: 81%
“…There are several lines of evidence to support this claim. First, very young children have been shown to use higher rate of postural corrections (Riach and Hayes 1987) which may be accounted for by the predominance of feedback responses (Haas et al 1989). The effective feedforward postural adjustments turn up later (Haas et al 1989) and partially replace this reactive strategy which results in a decrease of the COP frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Two functions have been attributed to the APAs since Belenkii et al's experiments (1967): The minimization and optimization of the centre of foot pressure (CoP) displacements. Previous findings related to APAs in children reported that this population is able to produce anticipatory activities in arm raising (Hay and Redon, 2001;Riach and Hayes, 1990), tiptoe standing (Haas et al, 1989), and gait initiation (Assaı¨ante et al, 2000;Ledebt et al, 1998;Malouin and Richards, 2000). The APAs are not innate in gait initiation and must undergo development before being systematic and functional (Hayes and Riach, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors examined APAs in a series of forward-oriented motor tasks, including stepping forward and initiating gait (Crenna and Frigo, 1991;Haas et al, 1989). Mouchnino et al (1992a,b) showed that a lateral leg raising movement to an angle of 45 deg was linked to CoP displacements towards the moving leg.…”
Section: Introductionmentioning
confidence: 99%